Stress in elite sport performers: A comparative study of competitive and organizational stressors - Hanton, S.; Fletcher, D.; Coughlan, G. (Journal of Sports Sciences, 2005)
The purpose of this study was to compare the content and quantity of competitive and organizational stressors in elite athletes. Ten international performers were interviewed about sources of stress. Content analysis of the data involved categorizing the demands associated primarily and directly with competitive performance (#CS=21) under the post hoc dimension "performance issues", and the demands associated primarily and directly with the sport organization (#OS=72) under one of the following four post hoc dimensions: "environmental issues", "personal issues", "leadership issues" and "team issues". Frequency analysis revealed that the participants mentioned the competitive stressors (S=95) less than the organizational stressors (S=215). Further analysis within these categories showed that the mean number of participants citing individual competitive stressors (M=4.52) was greater than the mean number of participants citing individual organizational stressors (M=2.99). The findings indicate that elite athletes experience and recall more demands associated primarily and directly with the sport organization than with competitive performance. Furthermore, this population appears more likely to mention similar competitive stressors but varied organizational stressors, probably because the former are inherent and endemic to elite sport, whereas the latter are essentially extraneous and widely distributed.